INTERNATIONAL DIABETES FEDERATION CONSENSUS ON DEFINITION OF THE METABOLIC SYNDROME: FACTS AND COMMENTS - M. N. Mamedov (Рациональная фармакотерапия в кардиологии)
International Diabetes Federation consensus, devoted to definition of the metabolic syndrome was published in 2006. The main statements of this document are presented and commented.